Effect of Cytochrome P450 Family 2 Subfamily R Member 1 Variants on the Predisposition of Coronary Heart Disease in the Chinese Han Population - Wang, Qi; Lin, Zhen; Chen, Hairong; Ma, Tianyi; Pan, Biyun (Frontiers in Cardiovascular Medicine, 2021)
Propose: Cytochrome P450 family 2 subfamily R member 1 (CYP2R1) variations can affect the activity of 25-hydroxylase, resulting in the deficiency of 25(OH)D, which leads to an increased incidence and mortality of coronary heart disease (CHD). The purpose is to assess the influence of CYP2R1 variants on CHD risk among the Chinese Han population. Methods: A total of 508 CHD patients and 510 healthy controls were enrolled. The MassARRAY platform completed genotyping of CYP2R1 variants. Odds ratios (ORs) with 95% confidence intervals (CI) were calculated using logistic regression analysis. Results: Rs6486205 (OR = 1.25, 95% CI: 1.05–1.50, p = 0.014), rs10741657 (OR = 1.29, 95% CI: 1.08–1.54, p = 0.005), and rs2060793 (OR = 1.27, 95% CI: 1.06–1.51, p = 0.009) were associated with the increased susceptibility to CHD in the whole subjects. Interestingly, the relationships between these variants and CHD risk were observed in the subjects with age >60 years, males or non-smoker. Additionally, the haplotypes Ars10741657Ars2060793 and Grs10741657Grs2060793 had the higher risk of CHD, and the combination (rs6486205 and rs10741657) was the best multi-locus model. Conclusion: Our study suggested the contribution of CYP2R1 polymorphisms to the increased CHD predisposition in the Chinese Han population. Furthermore, the risk association was related to confounding factors for CHD, including age, sex, and smoking. These findings might help to strengthen the understanding of the CYP2R1 gene in the occurrence of CHD.